Reproductive behavior of White-tailed Kites (Elanus leucurus) in the Pampas of Argentina - Baladrón, Alejandro Victor (2019)
The White-tailed Kite (Elanus leucurus) is a raptor that has been less studied in the Neotropics than in the Nearctic region, especially in relation to its reproductive behavior. In this study, we report information about the phenology and activity patterns of this raptor at the Pampas of Argentina. We found that White-tailed Kites have a prolonged breeding season, from October to May. Time-activity budgets of mating pairs indicated a pronounced division of roles in parental care between sexes. Females devoted most of their time to nest construction, incubation and chick care (80% of total time) and males to food provisioning and vigilance (70% of total time). We registered 11 cases of prey transfer from the male to the female. In four cases the transfer occurred in flight and in the remaining seven cases while individuals were perched. Our results agree with general patterns on breeding behavior of White-tailed Kites from North America, suggesting a consistent behavioral pattern throughout the species´ distribution.